Analisis Swot Atas Implementasi Strategi Pemasaran Produk Shiny Tea PT. Raja Rasa Alami Di Jakarta - B Say, Alfonsus (Journal of Economics & Business UBS, 2019)
SWOT analysis is the popular method to evaluate corpoarate business. PT Raja Rasa Alami (Shiny Tea) is engaged in food and baverage products that are marketed is a kind of buble tea.  During  the process of distributing the product the company experiences various obstacles, one of which is product branding that is not yet known to the public.  Due to the unpopular brand awernes problem, this study aims to: (1) To determine the value of the company's internal factors, the highest value of strength, and the weaknesses of the company. (2) To find out the value of the company's external factors, the greatest opportunities, and the smallest opportunities that the company has. (3) To find out the current condition of the company. (4) To find out what marketing strategies are right for the company to use. Qualitative methods and includes explorative descriptive research with the expose facto approach is the suitable method to describe the situation of the phenomena. The unit obsertvations are employees of the companya and buble tea consumers.  The results showed that the companies have better strengths than weaknesses, but companies have a higher threat of opportunity. The position of the company is currently in a position of business growth, but the employee is not ready to enter into competitiveness. And there is no regular review on capacity planning optimalization the impat to the distribution strategy.